2016
DOI: 10.15517/rbt.v64i4.21880
|View full text |Cite
|
Sign up to set email alerts
|

El jaguar Panthera onca (Carnivora: Felidae) en la Reserva de la Biosfera “El Cielo”, Tamaulipas, México

Abstract: The jaguar Panthera onca (Carnivora: Felidae) in "El Cielo" Biosphere Reserve, Tamaulipas, Mexico. Information on the ecology of jaguars (Panthera onca) in "El Cielo" Biosphere Reserve in Tamaulipas,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It's possible that the activity shown by pumas during the day in the ECBR is due to the presence of the jaguar and minimal human activity. Carrera-Treviño et al (2016) reported no sightings of pumas during daylight hours on the periphery of the ECBR probably because their study was carried out in disturbed areas and those with human settlements.…”
Section: Discussionmentioning
confidence: 99%
“…It's possible that the activity shown by pumas during the day in the ECBR is due to the presence of the jaguar and minimal human activity. Carrera-Treviño et al (2016) reported no sightings of pumas during daylight hours on the periphery of the ECBR probably because their study was carried out in disturbed areas and those with human settlements.…”
Section: Discussionmentioning
confidence: 99%